Long-term results of organ procurement from burn victims - Schmauß, Daniel; Bigdeli, Amir Khosrow; Hellmich, Susanne; Kremer, Thomas; Germann, Günter; Kneser, Ulrich; Megerle, Kai Oliver (Burns, 2017)
Background: With the increasing success of organ transplantation, many traditional contraindications to organ procurement are being reconsidered. Burn disease has constituted a traditional contraindication to solid organ procurement because of concerns that such organs may have been compromised by ischemia secondary to burn shock and contaminated by bacteremia. With the current shortage of solid organs, the transplant community continues to look for ways to increase the number of organ donors, including the use of marginal donors. Methods: Between 1999 and 2009 we have successfully procured 14 organs from four burn patients, who had suffered concurrent anoxic brain injury. There were one male and three female patients with an average age of 43.3 years and a total burned body surface area of 32.5%. Organ transplantation was performed at an average of 4.75days after the injury. Eight kidneys, three livers, two hearts and one pancreas were procured and transplanted into 13 patients. Results: We were able to follow-up on the organ recipients for an average of 80.5 months. The 5-year survival of the donated organs following transplant was 78.6% and the 5-year organ recipient survival was 92.3%. Conclusions: Organ procurement after burns is not contraindicated and transplantation can be performed with good long-term results.
Gesehen am 15.05.2018